Diagnostic Accuracy of Transvaginal Ultrasound versus Hysteroscopy in Detecting Endometrial Pathologies in Women with Abnormal Uterine Bleeding - Mian Waheed Ahmad, Saima Noreen, Ammara Mansoor, Tahira Akhtar, Sidra Gaffar, Alia Akram, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Abnormal uterine bleeding (AUB) is one of the most common gynecological complaints among women, often resulting from various benign and malignant endometrial pathologies. Accurate diagnosis is essential for appropriate management, and while transvaginal ultrasound (TVUS) is widely used as a non-invasive screening tool, hysteroscopy provides direct visualization of the uterine cavity and remains the gold standard for diagnosis. Objective: To compare the diagnostic accuracy of transvaginal ultrasound versus hysteroscopy in detecting endometrial pathologies in women presenting with abnormal uterine bleeding. Study Design & Setting: A cross-sectional comparative study conducted in the Department of Obstetrics and Gynecology Gujranwala Medical College, Gujranwala from Jan 2023 to June 2023. Methodology: A total of 150 women aged 30–60 years with AUB were included using non-probability consecutive sampling. All participants underwent TVUS followed by hysteroscopic evaluation, and histopathological examination of endometrial samples served as the gold standard. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy of both modalities were calculated. Results: The mean age of participants was 45.2 ± 7.8 years, with 62.7% being premenopausal. The most frequent pathologies on histopathology were endometrial polyp (24.0%) and hyperplasia (21.3%). TVUS showed sensitivity 82.8%, specificity 73.1%, PPV 87.3%, NPV 65.5%, and accuracy 83.5%. Hysteroscopy demonstrated higher sensitivity (94.9%), specificity (84.6%), PPV (93.3%), NPV (91.7%), and overall accuracy (93.3%). Conclusion: Hysteroscopy is a more accurate diagnostic tool than transvaginal ultrasound for identifying endometrial pathologies in women with AUB. Combining both modalities can enhance diagnostic reliability and guide effective management. Keywords: Abnormal uterine bleeding, diagnostic accuracy, endometrial pathology, hysteroscopy, transvaginal ultrasound